The Application of a Plant Biostimulant Based on Seaweed and Yeast Extract Improved Tomato Fruit Development and Quality - Giuseppe Mannino; Cristina Campobenedetto; Ivano Vigliante; Valeria Contartese; Carla Gentile; Cinzia M. Bertea (Biomolecules, 2020)
Plant biostimulants are under investigation as innovative products to improve plant production and fruit quality, without resulting in environmental and food contaminations. Here, the effects of the application of Expando, a biostimulant based on seaweed and yeast extracts, on plant productivity, fruit ripening times, and fruit quality of Solanum lycopersicum var. Micro-Tom were evaluated. After biostimulant treatment, a two-week reduction of ripening times and a concomitant enhancement of the production percentage during the earliest ripening times, in terms of both fruit yield (+110%) and size (+85%), were observed. Concerning fruit quality, proximate analysis showed that tomatoes treated with the biostimulant had better nutritional composition compared to untreated samples, since both the quality of unsatured fatty acids (C16:3ω3: +328%; C18:2ω6: −23%) and micronutrients essential for human health (Fe: +14%; Cu: +21%; Zn: +24%) were increased. From a nutraceutical point of view, despite strong changes in bioactive compound profile not being observed, an increase of the antioxidant properties was recorded in fruits harvested by plants treated with the biostimulant (2,2’-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS): +38%; 2,2-diphenyl-1-picrylhydrazyl (DPPH): +11%). In conclusion, the biostimulant application was able to reduce the ripening times and fruit size, while slightly increasing nutritional and nutraceutical values, leading to more marketable tomato fruits.